Norse mythology A to Z - Daly, Kathleen N.; Rengel, Marian (New York Facts on File, 2004)
Alphabetically listed entries identify and explain the characters, events, and important places of Norse mythology.
Includes bibliographical references (p. 113-114) and index.
Keywords: Mythology, Norse -- Encyclopedias; Scandinavia -- Religion -- Encyclopedias